Effect of heat treatment on microstructure and property of high vanadium wear‐resistant alloy. Issue 12 (10th December 2018) - Hui, L.; Han‐Guang, F.; Jiang, J.; Jun, W.
Abstract: In order to improve the properties of high vanadium wear‐resistant alloy and obtain the optimal process parameters, the effect of heat treatment on the microstructure and properties of high vanadium wear‐resistant alloy was studied by means of optical microscope, the scanning electron microscope, X‐ray diffraction, energy dispersive spectrometer, Rockwell and Vickers hardness tester. The results show that the microstructure of as‐cast high vanadium wear‐resistant alloy was composed of matrix and eutectic structure. The matrix was mainly composed of martensite and retained austenite, and the eutectics mainly included M7 C3 and VC type carbide. After quenching, the matrix structure of the alloy remains martensite and retained austenite. M23 C6 type carbide was precipitated while quenching at 1100 °C. The type of eutectic structure has no obvious change after tempering. Tempering has great influence on the amount of retained austenite in the matrix. The hardness of the alloy is the highest (about 69.1 HRC) when the quenching temperature and tempering temperature are 1000 °C and 550 °C respectively.